English Teachers’ Competence toward the Students Achievement - Umar; Nursyam (Universitas Sulawesi Barat, 2022)
This study was conducted to determine the competence of teachers in learning English and the inhibiting factors for learning English during the Covid-19 pandemic at smk yppp Wonomulyo. This research was conducted in August and September 2021 using a mix method through interview data collection techniques for English teachers at smk yppp Wonomulyo and collecting several documents related to teacher competence. As well as giving tests to students as quantitative data. Based on the results of the study, it is known that the competence of English teachers during the covid-19 pandemic at smk yppp Wonomulyo is good, the teacher has implemented designing, implementing and evaluating learning even though learning is done online, making strategies that are in accordance with online learning, teachers must make emergency rpp and evaluate learning despite the many shortcomings and difficulties in carrying out online learning. The inhibiting factors for learning English during the covid-19 pandemic are the lack of availability of learning resources, there are still students who do not have an Android cellphone, limited internet quota, there are still many students who are ignorant of online learning.